Water quality assessment for drinking water: case study at Mongkodou river, Ranau Sabah - Rohana Tair; Mohd Harun Abdullah; Hafizan Juahir; Baba Musta; Sahibin Abd Rahim; Fera Cleophas; Nur Zaida Zahari; Farrah Anis Fazliatul Adnan; Siti Aishah Mohd Ali; Kamsia Budin; Ahmad Norazhar Mohd Yatim (Faculty of Science and Natural Resources, UMS, 2024)
Monitoring water quality at the river is an initiative to identify the water resource’s status in certain areas. The water quality status is crucial for water resources as drinking water for human health. Mostly, rural areas are difficult to have treated water supply from government or any water supply agencies. So, the nearest river is an alternative for their water resources for drinking water and daily consumption. The aim of this study is to determine the river raw water quality in rural areas for drinking suitability. Mongkodou River has been selected for this study as it is in rural areas and near to the exMamut copper mining. In addition, this study also has an advantage in monitoring the possibility impact from the mining activities. The in-situ water quality parameters were measured by using ProDSS YSI multimeter. And, for heavy metals the water samples were collected by using polyethylene bottles in depth between 15 to 20 cm under the surface water and preserve it with HNO3 until <pH 2 before analysed with ICPOES. The water quality parameters are measured were TDS, TS, temperature, electrical conductivity (EC), DO, pH, turbidity, sulphate, chloride, TSS and heavy metals (Cu, Cr, Cd, Fe, Pb and Zn). The water quality parameter at Mongkodou river is still under the permissible National Standard for Drinking Water Malaysia except for TSS, and turbidity. For conclusion, Mongkodou river is classified as an unpolluted river and can be use for daily consumption but its not suitable for drinking water without treatment.